Market assessment and impact survey of the Public Education Programme (PEP) - the CARICOM Single Market and Economy (CSME) and the proposed Caribbean Court of Justice (Caribbean Media Consultants St. JosephTT, 2001)
Reports on the results of the survey and makes recommendations for the better execution of a PEP related to the implementation of the proposed Caribbean Court of Justice.
Keywords: MARKET STUDIES